RANCANG BANGUN GAME SIMULASI PEMBUATAN KECAP TRADISIONAL MAJALENGKA MENGGUNAKAN METODE MDLC BERBASIS ANDROID - Purnama, Crisda; Ade Bastian (Universitas Majalengka, 2021)
Majalengka is one of the regencies located in West Java Province with various cultures and culinary. The use of traditional soy sauce is less attractive than the use of modern soy sauce, thus the authors designed a simulation game for making traditional soy sauce Majalengka using the Multimedia Development Life Cycle (MDLC) method. Games are currently in great demand by various groups, especially children, which are used as educational tools to improve children's abilities, for example in the culinary field, which aims to create a conservation medium in the form of android-based educational games. With the existence of the traditional Majalengka soy sauce simulation game, it can make it easier for the introduction of making traditional soy sauce, this traditional soy sauce making simulation game is expected to be able to introduce the traditional Majalengka soy sauce to the community, especially in the Majalengka area.